Consumer behaviour toward modern food products and trends - Abdalrahman, Mohammed (Mednarodno inovativno poslovanje, 2019)
People practicing food buying and consumption activities in everyday of their life%s, therefore this study aims to highlight the main factors that could affect consumer attitudes towards novel food products and consumption trends. The study handled three main food consumption trends that are: sustainable food consumption, organic food consumption and genetically modified food consumption. In order to achieve the study objective, a desk research was conducted, and a through literature survey was carried out on the main factors that affect consumer attitudes toward novel food products and consumption patterns.
Keywords: consumer attitudes; genetically modified products; gensko spremenjeni izdelki; GMOs; GSO; novel food trends; novi prehranski trendi; organic food; organska hrana; stališča potrošnikov